ongenital malformations of lungs and mediastinum. Diagnostics. Treatment. - S.A. Karavayeva; T.K. Nemilova; A.N. Kotin; T.V. Omelchenko; S.V. Starevskaya; S.D. Popov; N.A. Ilyin; N.A. Borisova (Bukovynian State Medical University, 2019)
Congenital malformations of lungs and mediastinum in newborns and infants are relatively new problem of neonatal surgery. Early prenatal detection is possible from 18-20 weeks of gestation. During last 15 years in St. Petersburg Center of neonatal surgery 95 patients with congenital malformations of lungs and mediastinum were treated. The main method of diagnostic of these states is computer tomography. 72 patients were operated. Indications for early surgical treatment are the high risk of infection and malignancy, increase of intrathoracic pressure, compression of vital organs and mediastinal shift.